Megestrol Acetate as a Treatment for Anorexia in Hemodialysis Patients - Teruel, José L.; Fernández-Lucas, Milagros; Marcén, Roberto; Gomis, Antonio; Elías, Sandra; Raoch, Viviana; Quereda, Carlos (Journal of Nutritional Therapeutics, 2014)
Background: The aim of this study was to evaluate the effectiveness of megestrol acetate as a treatment for anorexia in hemodialysis patients. Materials and Methods: From 1st January 2008 to 31st December 2010, 29 patients in our Hemodialysis Unit were treated with megestrol acetate (initial dose: 160 mg / day) for anorexia associated with a decrease in dry body weight. Sixteen patients had a protein-energy wasting syndrome. Results: Appetite improved in 25 patients, but the initial dose of megestrol acetate had to be increased in 8 patients. At three months, there was an increase in dry body weight (63.4 vs 61.9 kg, p=0.002), serum albumin level (3.98 vs 3.77 g/dl, p<0.001), serum creatinine level (10.5 vs 9.6 mg/dl, p=0.016) and protein catabolic rate (1.21 vs 0.98 g / kg / day, p < 0.001). The response was independent of the cause of anorexia. A bioelectrical impedance analysis, carried out in 9 patients, showed that treatment with megestrol acetate increased the body cell mass and changed the distribution of body water by increasing intracellular water. The megestrol acetate treatment was well-tolerated and no patients left the study due to side effects or adverse reactions. Conclusions: Megestrol acetate improves appetite and nutritional parameters in anorexic patients treated with maintenance hemodialysis.